Tax Planning, Accounting Conservatism, and Tax Disputes: Evidence from the Energy Sector in Indonesia - Muhamad Arif Gumelar; Achmad Fadjar (STIE Amkop Makassar, 2026)
Discrepancies in interpreting tax regulations between taxpayers and tax authorities frequently act as the main catalyst for tax disputes. Therefore, this study was conducted to examine the impact of tax planning on the likelihood of tax disputes, while also evaluating the role of accounting conservatism as a mediating variable. The scope of this research covers companies within the Oil & Gas Production & Refinery sub-sector listed on the Indonesia Stock Exchange (IDX) over the 2021–2025 observation period. A saturated sampling (census) approach was employed, yielding 13 corporate entities as the unit of analysis. Hypothesis testing was executed utilizing the Path Analysis technique through SPSS statistical software. The empirical findings demonstrate that tax planning exerts a positive and significant impact on the escalation of tax disputes. Conversely, tax planning was found to have no meaningful influence on the level of corporate accounting conservatism. Moreover, accounting conservatism is proven incapable of mediating the relationship between tax planning and tax disputes. The implications of this research assert that intensive tax planning practices directly elevate the risk of fiscal interpretation friction, irrespective of whether a company adopts conservative financial reporting principles.